IMPLEMENTASI NILAI KEMANUSIAAN DALAM AL-QUR’AN PADA INTERAKSI GURU DAN PESERTA DIDIK DI SMP NEGERI 1 ULUIWOI - Ulfa Rahma; Mukayat Al Amin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the humanistic values in the Qur’an that are relevant to educational interaction, their implementation in teacher student interaction, and the factors influencing their application at SMP Negeri 1 Uluiwoi. This research employed a qualitative approach with a descriptive analytical method. Data were collected through observation, in depth interviews, and documentation involving the principal, teachers, and students, and were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the dominant Qur’anic humanistic values in educational interaction include respect for human dignity, justice, compassion and empathy, as well as moral responsibility and exemplarity. These values have been implemented in a relatively humanistic and dialogical manner in both classroom and school interactions, although their application has not been entirely consistent in certain situations. Supporting factors include teachers’ religious understanding and a conducive school culture, while inhibiting factors involve time constraints, teachers’ administrative workload, and students’ social environments. This study underscores that integrating Qur’anic humanistic values into educational interaction is essential for strengthening character education within the framework of Islamic education.